2021
DOI: 10.1021/acs.jpcc.1c00561
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Oxo Active Sites in the 8MR of Zeolite Mordenite: DFT Investigation of the Impact of Acid Sites on Methanol Yield and Selectivity

Abstract: There is significant interest in improving methanol yields from methane in copper-exchanged zeolites. Interestingly, zeolites with proton, H + , precursors provide greater methanol yields and selectivities than zeolites from sodium, Na + , precursors. There is however no quantitative description of the origins of these differences. Here, we use the density functional theory to probe differences in the properties of copper-oxo species in the 8-membered ring of zeolite mordenite, MOR. We focus only on [Cu 3 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…This agrees quite well with our previous report. [40] We note also that Zhao et al found very high barriers for methane CÀ H activation trans-μ-1,2-peroxo dicopper sites in the 12MR of MOR. [16] The high barriers for methane activation by [Cu 2 O 2 ] 2 + species in MOR is in contrast to low barriers in the MFI framework.…”
Section: Cà H Activation By [Cu 2 O 2 ] 2 +mentioning
confidence: 65%
See 4 more Smart Citations
“…This agrees quite well with our previous report. [40] We note also that Zhao et al found very high barriers for methane CÀ H activation trans-μ-1,2-peroxo dicopper sites in the 12MR of MOR. [16] The high barriers for methane activation by [Cu 2 O 2 ] 2 + species in MOR is in contrast to low barriers in the MFI framework.…”
Section: Cà H Activation By [Cu 2 O 2 ] 2 +mentioning
confidence: 65%
“…Details of these periodic DFT calculations are like those from our previous reports. [40,41] Except where otherwise stated, the energies of the intermediates and transition state species are provided relative to the energies of the active site and gaseous methane, I. In I, the electronic energies from periodic DFT for the intermediate or transition state species is E pecie while those for the active site and methane are E acive ie and E CH4 , respectively.…”
Section: Computational Details and Modelsmentioning
confidence: 99%
See 3 more Smart Citations